Case report: Better late than never, but sooner is better: switch from CSII to sulfonylureas in two patients with neonatal diabetes due to KCNJ11 variants - Mancioppi, Valentina; Pozzi, Erica; Zanetta, Sara; Missineo, Anna; Savastio, Silvia; Barbetti, Fabrizio; Mellone, Simona; Giordano, Mara; Rabbone, Ivana (Frontiers in Endocrinology, 2023)
Neonatal diabetes mellitus (NDM) is a rare genetic disease characterized by severe hyperglycemia requiring insulin therapy with onset mostly within the first 6 months and rarely between 6-12 months of age. The disease can be classified into transient (TNDM) or permanent neonatal diabetes mellitus (PNDM), or it can be a component of a syndrome. The most frequent genetic causes are abnormalities of the 6q24 chromosomal region and mutations of the ABCC8 or KCNJ11 genes coding for the pancreatic beta cell's potassium channel (KATP). After the acute phase, patients with ABCC8 or KCNJ11 mutations treated with insulin therapy can switch to hypoglycemic sulfonylureas (SU). These drugs close the KATP channel binding the SUR1 subunit of the potassium channel and restoring insulin secretion after a meal. The timing of this switch can be different and could affect long-term complications. We describe the different management and clinical outcome over the time of two male patients with NDM due to KCNJ11 pathogenetic variants. In both cases, continuous subcutaneous insulin infusion pumps (CSII) were used to switch therapy from insulin to SU, but at different times after the onset. The two patients kept adequate metabolic control after the introduction of glibenclamide; during the treatment, insulin secretion was evaluated with c-peptide, fructosamine, and glycated haemoglobin (HbA1c), which were within the normal range. In neonates or infants with diabetes mellitus, genetic testing is an indispensable diagnostic tool and KCNJ11 variants should be considered. A trial of oral glibenclamide must be considered, switching from insulin, the first line of NDM treatment. This therapy can improve neurological and neuropsychological outcomes, in particular in the case of earlier treatment initiation. A new modified protocol with glibenclamide administered several times daily according to continuous glucose monitoring profile indications, was used. Patients treated with glibenclamide maintain good metabolic control and prevent hypoglycemia, neurological damage, and apoptosis of beta cells during long‐term administration.